Politik Pembangunan Daerah Kabupaten Pakpak Bharat Tahun 2010-2015 - SIHOMBING, DWI AYU RAFITA; KUSMANTO, HERI (Politeia: Jurnal Ilmu Politik, 2017)
The government Pakpak Bharat (2010-2015) has been running for four years. There are many programs and strategies that create better development conditions.This study describes the political development in the Pakpak bharat Regency. The focus is to discuss the orientation or development policy objectives in the government Pakpak Bharat 2010-2015. This study found there are five things that the main orientation of development in Pakpak Barat regency, namely in the areas of infrastructure, education; health; the field of economy; and the bureaucracy.Improving human resources is one focus of the governments work, namely by increasing the development budget of education, as well as other programs that improve the level of education.In the health sector, there is an increase in hospital facilities, community health centers, health care centers maid, Posyandu and polindes.The study used the approach to political development. This study method is descriptive. Collecting data with depth interview. Analysis of data using qualitative analysis. Keywords: Political development, public policy, public mobility.